1996
DOI: 10.1111/j.1751-1097.1996.tb02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Magnesium‐L‐Ascorbyl‐2 Phosphate Against Skin Damage Induced by UVB Irradiation

Abstract: The protective effect of magnesium-L-ascorbyl-2-phosphate (MAP) on cutaneous photodamage such as lipid peroxidation and inflammation induced by ultraviolet B (UVB) exposure (290-320 nm, max. 312 nm) was investigated using hairless mice. When MAP was administered intraperitoneally to mice at a dose of 100 mg of ascorbic acid (AS) per kg body weight base immediately before irradiation (15 kj/m2), the expected increases in thiobarbituric acid reactive substance (TBARS) formation in skin and serum sialic acid, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…79 Because of its instability in aqueous solution, esters like magnesium ascorbyl-2-phosphate (MAP) with similar properties have been used. 80 MAP was found to reduce pigmentation significantly in 19 of 34 patients with melasma and senile freckles but only in three of 25 patients with normal skin. 81 Ascorbic acid can be used alone or in combination therapy.…”
Section: Ascorbic Acidmentioning
confidence: 84%
“…79 Because of its instability in aqueous solution, esters like magnesium ascorbyl-2-phosphate (MAP) with similar properties have been used. 80 MAP was found to reduce pigmentation significantly in 19 of 34 patients with melasma and senile freckles but only in three of 25 patients with normal skin. 81 Ascorbic acid can be used alone or in combination therapy.…”
Section: Ascorbic Acidmentioning
confidence: 84%
“…Besides, natural extracts such as mulberry extract(paper mulberry), licorice extract(glabridin), bearberry extract, A.patula and A. viscida and green tea extract are also known as whitening materials 3 . AsA affects collagen synthesis, drug-metabolizing enzyme, production of interferon, antiviral, antibacterial, and antioxidization and photoprotective actions 13 . AsA does not possess intrinsic absortive capacity for UV radiation and are believed to act after UV radiation has penetrated the skin and interacted with resident skin chromophores to generate reactive oxygen radicals species 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, using preclinical models, Kobayashi et al (1996) reported that intraperitoneal (100 mglkg body weight) administration of magnesium-L-ascorbyl-2-phosphate to mice induced a significantly decreased lipid peroxidation in skin, measured by TBARS assay (thiobarbituric acid reactive substance). Chandra Jagetia et al (2003) reported that daily administration of 250 mg/kg body weight of vitamin C before exposure to gamma rays resulted in a significant increase in the activities of superoxide dismutase and glutathione peroxidase as well as glutathione content in the irradiated mouse skin.…”
Section: Vitamin C and Photoprotectionmentioning
confidence: 99%